Factors Determining Financial Performance in Local Government (An Empirical Study on Regencies/Cities Across Indonesia for the Years 2017-2019)". - Salsabila, Alifa Khansa; Bawono, Andy; Conteh, Abdul (Formosa Journal of Science and Technology, 2024)
This study aims to identify the determine of financial performance on Local Government in Indonesia 2017-2019. This study used five variables, namely local taxes; regional retribution; capital expenditures; asset turnover; and leverage. This research is a quantitative study. The performance measure used in this study is the ratio of regional independence. The sample used in this study were 1479 which consisted of 493 data from districts and cities in Indonesia. Sampling technique with method purposive sampling. The data source in this study was secondary data where the data obtained were in the form of documents. Testing the data using multiple linier regression. The results show that regional retribution, capital expenditure, and asset turnover have a significant effect to the financial performance on local government. Whereas the local taxes and leverage have no significant effect to financial performance on local government.